Neoadjuvant chemoradiotherapy up-regulates PD-L1 in radioresistant colorectal cancer - Sung Uk Bae; Hye Won Lee; Jee Young Park; Incheol Seo; Jae-Min Cho; Jin Young Kim; Ju Yup Lee; Yoo Jin Lee; Seong Kyu Baek; Nam Kyu Kim; Sang Jun Byun; Shin Kim (Clinical and Translational Radiation Oncology)
Background: Combining radiotherapy (RT) with immune checkpoint inhibitors (ICIs) is a promising strategy that can enhance the therapeutic efficacy of ICIs. However, little is known about RT-induced changes in the expression of immune checkpoints, such as PD-L1, and their clinical implications in colorectal cancer (CRC). This study aimed to investigate the association between responsiveness to RT and changes in PD-L1 expression in human CRC tissue and cell lines. Methods: Tissue specimens from preoperative biopsy via sigmoidoscopy and surgical resection were obtained from 24 patients with locally advanced rectal cancer (LARC) who underwent neoadjuvant chemoradiation therapy (CRT) between August 2016 and December 2017. Immunohistochemistry for PD-L1 in formalin-fixed paraffin-embedded tissue was performed from the endoscopic biopsy and surgical specimens. RNA sequencing was performed using 11 pairs of human LARC tissues before and after irradiation. After exposing human CRC cells to radiation, we investigated changes in the expression levels of PD-L1 and its regulatory signaling pathways. Results: Patients were classified by tumor regression grade into responders (grade 2; 9 patients, 37.5 %) and non-responders (grades 3, 4, or 5; 15 patients, 62.5 %). In the non-responder group, 13 patients had low PD-L1 expression, but neoadjuvant CRT increased PD-L1 expression in 7 patients (53.9 %) (McNemar’s test, p=0.034). CRT up-regulated PD-L1 in non-responder LARC tissues. Similarly, radiation increased PD-L1 in radioresistant DLD-1 cells more than in radiosensitive HCT116 cells, also affecting PD-L1-regulating genes and immune checkpoints in CRC cells. Conventional fractionated radiation treatment further increased PD-L1 in DLD-1 cells compared to HCT116 cells. Conclusions: This study demonstrated that radiation induces an increase in PD-L1 expression, which is more pronounced in radioresistant CRC, proving the theoretical framework for a combined treatment strategy with a PD-L1 blockade for locally advanced rectal cancer.